2013
DOI: 10.1007/s11010-013-1910-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of prosurvival signaling pathways during the memory phase of volatile anesthetic preconditioning in human myocardium: a pilot study

Abstract: According to a compelling body of evidence anesthetic preconditioning (APC) attenuates the deleterious consequences of ischemia-reperfusion and protects the heart through a mechanism similar to ischemic preconditioning. The present study was purported to investigate the intracellular signaling pathways activated in human myocardium in response to a preconditioning protocol with two different volatile anesthetics, namely isoflurane and sevoflurane. To this aim, phosphorylation of PKCα and -δ, ERK1/2, Akt, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Volatile anesthetics can protect from infarction and increase the phosphorylation of Akt (12,23). We cannot exclude that the use of volatile anesthetics contributes to the increased phosphorylation of Akt at early reperfusion in both I/R and IPC.…”
Section: Limitationsmentioning
confidence: 93%
“…Volatile anesthetics can protect from infarction and increase the phosphorylation of Akt (12,23). We cannot exclude that the use of volatile anesthetics contributes to the increased phosphorylation of Akt at early reperfusion in both I/R and IPC.…”
Section: Limitationsmentioning
confidence: 93%
“…Ингибирование фосфо-ERK1/2 (центральной MAP-киназы) частично отменя-ет индуцированные изофлураном накопление HIF-1α и нейропротекцию. Изофлуран увеличивает уровень мРНК индуцибельной NO-синтазы [19,20].…”
Section: фармакологический запуск прекондиционированияunclassified
“…While this has yet to be further explored, the regulation of protein kinase C activity is a potential candidate. Isoflurane and sevoflurane activate multiple isoforms of protein kinase C [58], which itself has been identified as an up-regulator of HIF-1α via inhibition of HIF-1α degradation [59]. Therefore, isoflurane could be regulating HIF-1α via indirectly inhibiting HIF-1α degradation through the translation of protein kinase C. Interestingly, exposure to the intravenous anesthetic propofol results in a reduction of HIF-1α protein levels, possibly via the suppression of HIF-1α accumulation [60] or by inhibiting HREs [61].…”
Section: Volatile Anesthetics Regulate Hif-1αmentioning
confidence: 99%
“…Preconditioning with isoflurane ameliorates neuronal loss from ischemia in rats [65] and, interestingly, dose-dependently prevents neurotoxicity from subsequent prolonged exposure to volatile anesthetics in rat primary cortical neurons and pheochromocytoma neurosecretory cells with overexpression of Alzheimer's mutated presenilin-1 [67]. Importantly, animal research has suggested a role of HIF-1α up-regulation in the mechanisms underlying isoflurane and sevoflurane preconditioning protection in rabbits [57] and rats [58], respectively. Taken together with the aforementioned research, it appears that volatile anesthetics, via the up-regulation of HIF-1α, can be either neuroprotective or neurotoxic, depending on the context in which they are given.…”
Section: Beneficial Effectsmentioning
confidence: 99%
See 1 more Smart Citation